PERBANDINGAN HASIL UJI EKSTRAKSI CAMPURAN AC-BC MENGGUNAKAN METODE REFLUKS DAN METODE SENTRIFUS - Satryo, Rahmawan Budi; Sulistyono, Sonya; Hayati, Nunung Nuring (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Bitumen extraction tests aim to separate a mixture of asphalt paving mixtures and to determine which are made in accordance with the mix plan. In general, using a reflux and centrifuge method. At reflux method, bitumen separation process using the evaporation method, whereas the centrifuge method, the separation processes using a rotation method of extraction tools. The purpose of this study to determine whether the extraction of the AC-BC mixture using two methods above have significant differences using a statistical test. Based on the results of the testing that has been done, the result are different, but not significant in statistical test t-test. From the results of hypothesis testing the value obtained tcount (2.197) < ttable (2.4469) on 5.5% asphalt content, value of tcount (1.767) < ttable (2.4469) on 6% asphalt content, and tcount (0.201) < ttable (2.4469) on 6.5% asphalt content. While on F-test obtained different results, for sample testing with value of Fcount (520.1312) > Ftable (3.284), and there are significant differences between the methods of extraction with value of Fcount (97.779) > Ftable (5.980), and there is no interaction between testing methods with bitumen content with value of Fcount (0.3061) < Ftable (4.560).